Pengaruh Pemberdayaan Keluarga Penderita Tuberculosis Paru terhadap Kemampuan Melaksanakan Tugas Kesehatan Keluarga di Wilayah UPTD Puskesmas Rengas Kota Tangerang Selatan - Ibnu Fauzi; Dewi Fitriani; Siti Chasani (PT Pustaka Cendekia Publisher, 2025)
Pulmonary tuberculosis healing takes a long time. These were any problems that often occurs in the care and treatment of pulmonary tuberculosis in Indonesia. Family members should be empowered to be able to carry out the duties of health, to avoid mistakes in patient care at home. The purpose of this Study The Influence Of Empowering Families With Pulmonary Tuberculosis On Ability To Perform Family Health Duties In The UPTD Puskesmas Area, Tangerang Selatan. Methods this research is a quantitative research using the method of research is a Quasi Experiment is quantitative research. One Group Pretest & Posttest Design without a control group but has already done a first observation (pretest) that allows researchers can test the changes that occur after the experiment (posttest). The population in this study were mothers who had children aged (6-12) years i.e. there are 100 of the population, 80 respondents with purposive sampling method. Data analysis using Wilcoxon test. From the results Intervention results showed that the ability to carry out family health tasks which includes most of the known health problems (100%) category of good, take the right decisions most of the action (97.5%) categories of good, giving care to sick family (95.0%) categories of good, maintaining physical environments that support health home (87.%) categories of good, using the majority of health facilities (77.5%) categories of good. Statistical test results obtained family empowerment pulmonary TB patients can improve the ability of family task of family health (p=0.000). Conclusion: Family empowerment affect the family ability to carry out family health tasks to prevent, to care and to cure pulmonary tuberculosis, which includes the known health problems, take the right decisions, giving care to sick family, maintaining physical environments that support health home, using the majority of health facilities.